The digital defence against cyberbullying: A systematic review of tech-based approaches - Chan, Nee Nee; Nadia Samsudin; Ho, Meng Chuan; Mohamad Ikhram Mohamad Ridzuan; Ooi, Pei Boon; Ani Munirah Mohamad; Herbert Scheithauer (Cogent Education, 2023)
Cyberbullying, which has been exacerbated by the widespread use of smartphones and the increasing stress associated with the pandemic, needs the promotion of positive online behaviour, cyberbullying awareness, and victim support. The PRISMA technique is used in this review to identify effective preventative tools and intervention options. Eleven studies met our inclusion criteria and were selected for review. A quality assessment was conducted. Upon thorough evaluation of the included studies, the intervention data was compiled in a narrative format. Using thematic analysis, we explored the effectiveness of technological interventions for preventing cyberbullying comprehensively. Technology-driven strategies for identifying and combating cyberbullying in educational settings, such as language-specific cyberbullying detection tools, IRCB programmes for empowering teenagers, and technologies such as CREEP Semantic Technology and CREEP Virtual Coach, have showed potential. TIPIP and the #WIIWY movement have also assisted to raise awareness and educate people about cyberbullying. However, more research is required to design targeted interventions that address varied demographics and circumstances, while including parents and taking the target audience’s age into account remains critical for effective technology-driven educational interventions and digital advocacy.